Remembering Whitney : my story of love, loss, and the night the music stopped - Houston, Cissy (HarperCollins, 2013)
The Grammy Award-winning American soul and gospel singer and mother of Whitney Houston reflects on her daughter's life, the events that led up to her death and the aftermath of a senseless tragedy.